The effects of the vision on the central opacity and the positions of the curves invers for the brightness of the assumed elliptic sphere - Saad Younis; Omer Salih (College of Education for Pure Sciences, 2006)
The seeing effects on spherical symmetric Elliptical galaxy type EO following the r1/4- model has been calculated by using two type of the point spread function the Gaussian and Moffat functions . This study showed that the amount of central dimming Au;(0) for the seeing convolved Elliptical galaxy have an exponentially relationship with the reduced central dispersion value (a / re) of the point spread function , also the same proportion has been found for changeable positions r± for the seeing convolved surface brightness profiles . The relationships for the central dimming Au(0) and the changeable positions r± as a function of the reduced central dispersion have been found.